2019
DOI: 10.1016/s1872-2067(19)63293-6
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial engineering of graphitic carbon nitride (g-C3N4)-based metal sulfide heterojunction photocatalysts for energy conversion: A review

Abstract: As one of the most appealing and attractive technologies, photocatalysis is widely used as a promising method to circumvent the environmental and energy problems. Due to its chemical stability and unique physicochemical, graphitic carbon nitride (g-C3N4) has become research hotspots in the community. However, g-C3N4 photocatalyst still suffers from many problems, resulting in unsatisfactory photocatalytic activity such as low specific surface area, high charge recombination and insufficient visible light utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
152
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 451 publications
(167 citation statements)
references
References 409 publications
0
152
0
1
Order By: Relevance
“…Au single atoms on amino‐group‐enriched graphitic carbon nitride (U‐ACN) was synthesized through a mild and eco‐friendly urea reduction method (Figure a; see experimental details in the Supporting Information). The mixture of melamine and urea was calcined at 550 °C in air for 4 h, which led to the formation of graphitic carbon nitride (CN) through polycondensation . Then, urea, acting as the pH regulator, was added to the suspension of CN and HAuCl 4 in an 80 °C oil bath to facilitate the formation of Au‐containing precipitate AuCl 4− j (OH) j on CN .…”
Section: Figurementioning
confidence: 99%
“…Au single atoms on amino‐group‐enriched graphitic carbon nitride (U‐ACN) was synthesized through a mild and eco‐friendly urea reduction method (Figure a; see experimental details in the Supporting Information). The mixture of melamine and urea was calcined at 550 °C in air for 4 h, which led to the formation of graphitic carbon nitride (CN) through polycondensation . Then, urea, acting as the pH regulator, was added to the suspension of CN and HAuCl 4 in an 80 °C oil bath to facilitate the formation of Au‐containing precipitate AuCl 4− j (OH) j on CN .…”
Section: Figurementioning
confidence: 99%
“…They found that the formation of Z-scheme heterostructures between ZnO and CdS could effectively prolong the lifetime of photogenerated e − , reaching a 14-fold improvement in H 2 evolution performance compared with that of pure CdS. Since then, numerous direct Z-scheme CdS-based photocatalysts have been applied in photo-catalytic H 2 generation applications [334], including CdS/ WO 3−x [222], FeC 2 O 4 •2H 2 O/CdS [335], CdS/WO 3 [165,301], CdS/MoO 3−x [336], CdS/g-C 3 N 4 [337,338], CoWO 4 /CdS [44], CdS/Fe 2 O 3 [179], CdS/BiVO 4 [339], TiO 2 /CdS [329,340,341], CdS/CdWO 4 [219,342], ZnO/ CdS [306] and CdS/PI [217]. In our previous study, we reported the fabrication of 2D/2D CdS/g-C 3 N 4 direct Zscheme heterojunction nanocomposites through the insitu growth of 2D CdS NSs on 2D g-C 3 N 4 NSs [338].…”
Section: Direct Z-scheme Heterojunctionmentioning
confidence: 99%
“…In recent years, g‐C 3 N 4 photocatalysts with Z‐scheme heterojunction have gained extensive attention due to its special charge transfer mechanism in degrading the organic pollutants, which can prominently enhance the photocatalytic efficiency . The advantages of Z‐scheme photocatalysts are: construction cost reduction, electron–hole separation efficiency improvement, removal of light‐shielding effect, and redox ability optimization .…”
Section: Photocatalysismentioning
confidence: 99%